Habitat of juvenile Caribbean reef sharks, Carcharhinus perezi, at two oceanic insular marine protected areas in the southwestern Atlantic Ocean: Fernando de Noronha Archipelago and Atol das Rocas, Brazil - Garla, R. C.; Chapman, D. D.; Shivji, M. S.; Wetherbee, B. M.; Amorim, A. F. (Elsevier B.V., 2006)
Habitat of juvenile Caribbean reef sharks, Carcharhinus perezi (Carcharhinidae), was identified using fishing surveys and capture of immature specimens at two Brazilian insular sites in the southwestern Atlantic Ocean, Fernando de Noronha Archipelago and Atol das Rocas. Standardized sampling at Fernando de Noronha indicated that parturition occurred from February to April and that a wide depth-range (at least 5-30 m) along the insular shelf was used by immature sharks throughout the year. The catch-per-unit effort of C. perezi was significantly higher inside than outside a marine protected area at this location, suggesting that these sharks are more common in pans of the reef least disturbed by human activities. More limited sampling at Atol das Rocas suggested that juvenile C. perezi occurred at similar depths and utilized similar substrate as sharks at Fernando de Noronha. These findings suggest that successful conservation and management of this economically important, protected species will need to include conservation of habitat around insular reef systems. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Caribbean reef shark; juvenile habitat; nursery area; parturition; reproduction; marine protected area